Renal Resistive Index on Intensive Care Unit Admission Correlates With Tissue Hypoperfusion Indices and Predicts Clinical Outcome. Issue 4 (3rd April 2022) - Fotopoulou, Georgia; Poularas, Ioannis; Kokkoris, Stelios; Charitidou, Efstratia; Boletis, Ioannis; Brountzos, Elias; Benetos, Athanasios; Zakynthinos, Spyros; Routsi, Christina
ABSTRACT: Background: Renal resistive index (RRI) has been used to evaluate renal blood flow. Our aim was to investigate the relation between RRI and global tissue hypoperfusion indices and their association with clinical outcome, in intensive care unit (ICU) patients. Methods: RRI was measured within 24 h of ICU admission. Gas exchange and routine hemodynamic variables at the time of RRI assessment were recorded. An elevated RRI was defined as >0.7. The ratio of central venous-to-arterial carbon dioxide partial pressure difference by arterial-to-central venous oxygen content difference (P(cv-a) CO2 /C(a-cv) O2 ) and lactate were used as global tissue hypoperfusion indices. Results: A total of 126 patients were included [median age 61 (IQR 28) years, 74% males]. P(cv-a) CO2 /C(a-cv) O2 ratio and arterial lactate were significantly higher in patients with RRI >0.7 compared with those with RRI ≤0.7 [2.88 (3.39) vs. 0.62 (0.57) mmol/L and 2.4 (2.2) vs. 1.2 (0.6)] respectively, both P < 0.001)]. RRI was significantly correlated with P(cv-a) CO2 /C(a-cv) O2 ratio and arterial lactate for the whole patient population (rho = 0.64, both P < 0.0001) and for the subset of patients with shock (rho = 0.47, P = 0.001; and r = 0.64, P < 0.0001 respectively). Logistic regression models showed a significant association between RRI and P(cv-a) CO2 /C(a-cv) O2 ratio with clinical outcome. The combination of RRI with P(cv-a) CO2 )/(C(a-cv) O2 ratio and lactate better predicted mortality than RRI alone [AUC 84.8% (95% CI 5.1% –94.4%)] vs. [AUC 74.9% (95% CI 61%–88.8%)] respectively, P < 0.001. Conclusions: Renal blood flow assessed by RRI, on ICU admission, correlates with global tissue hypoperfusion indices. In addition, RRI in combination with tissue perfusion estimation better predicts clinical outcome than RRI alone.